Circadian Rhythms in the CNS and Peripheral Clock Disorders: The Circadian Clock and Hyperlipidemia - Takashi Kudo; Kazumasa Horikawa; Shigenobu Shibata (Journal of Pharmacological Sciences, 2007)
A circadian clock controls various physiological and behavioral rhythms. In mammals, a master circadian clock exists in the suprachiasmatic nucleus of the hypothalamus, and slave oscillators can be found in most tissues. These circadian oscillations are controlled by “clock genes”. The negative feedback loop is thought to function as a molecular mechanism of the circadian clock. It is plausible that clock genes may control lipid metabolism through so-called clock-controlled genes and that lipid metabolism-related clock-controlled genes may play important roles in the circadian change of lipid metabolism. Recently research has focused on the relationships between the clock system and lipid metabolism. In this review, we discuss the following items: 1) circadian clock system, 2) effect of the diet on clock gene expression, 3) effect of clock mutation on lipid metabolism, and 4) effect of streptozotocin-induced diabetes and ob mutation on clock gene expression and lipid metabolism. In this review we have summarized how the circadian clock affects lipid metabolism through the expression of lipid metabolism-related clock-controlled genes and at the same time discussed how abnormal metabolism of lipid affects the expression of clock genes. Further experiments are needed to elucidate the detailed mechanism of interaction between clock genes and lipid metabolisms. Keywords:: circadian, clock gene, rhythm, lipid metabolism, clock-controlled gene